Quality of Acute Stroke Care at Primary Stroke Centers Before and After Certification in Comparison to Never-Certified Hospitals - Shkirkova, Kristina; Wang, Theodore T.; Vartanyan, Lily; Liebeskind, David S.; Eckstein, Marc; Starkman, Sidney; Stratton, Samuel; Pratt, Franklin D.; Hamilton, Scott; Kim-Tenser, May; Conwit, Robin; Saver, Jeffrey L.; et al. (Frontiers in Neurology, 2020)
Background and Purpose: Primary stroke center (PSC) certification is associated with improvements in stroke care and outcome. However, these improvements may reflect a higher baseline level of care delivery in hospitals eventually achieving certification. This study examines whether advancements in acute stroke care at PSCs are due to certification or factors intrinsic to the hospital. Methods: Data was obtained from the Field Administration of Stroke Therapy-Magnesium (FAST-MAG) trial with participation of 40 Emergency Medical System agencies, 315 ambulances, and 60 acute receiving hospitals in Los Angeles and Orange Counties. Subjects were transported to one of three types of destinations: PSC certified hospitals (PSCs), hospitals that were not PSCs at time of enrollment but would later become certified (pre-PSCs), and hospitals that would never be certified (non-PSCs). Metrics of acute stroke care quality included time arrival to imaging, use of intravenous tPA, and arrival to treatment. Results: Of 1700 cases, 856(50%) were at certified PSCs, 529(31%) were at pre-PSCs, and 315 (19%) were at non-PSCs. Mean(SD) was 33min (±76.1) at PSCs, 47(±86.6) at pre-PSCs, and 49(±71.7) at non-PSCs. Of 1223 cerebral ischemia cases, rate of tPA utilization was 43% at PSCs, 27% at pre-PSCs, and 28% at non-PSCs. Mean ED arrival to thrombolysis was 71(±32.7) at PSC, 98(±37.6) at pre-PSC, and 95(±45.0) at non-PSCs. PSCs had improved time to imaging (p=0.014), percent tPA use (p<0.001), and time to treatment (p=0.003). Conclusions: Stroke care at hospitals prior to PSC certification is equivalent to care at non-PSCs.